2007
DOI: 10.2138/am.2007.2438
|View full text |Cite
|
Sign up to set email alerts
|

Laser Raman microspectrometry of metamorphic quartz: A simple method for comparison of metamorphic pressures

Abstract: A Laser Raman microspectrometry method was applied to metamorphic quartz in quartz-eclogite-, epidote-amphibolite-, and amphibolite-facies rocks to assess the quantitative correlation between the Raman frequency shift and metamorphic pressure. Quartz crystals sealed in garnet and other phases have a higher frequency shift than those in the matrix. Furthermore, the quartz inclusions show a frequency shift specifi c to the individual host crystals in eclogites (garnet ≈ kyanite > omphacite ≈ epidote). These obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 56 publications
5
154
1
Order By: Relevance
“…For different UHPM complexes the maximum upshift of the main Raman quartz bands (up to 477 cm À1 ) was documented for partly transformed coesite inclusions , corresponding to residual pressures of up to 1.6 GPa, (using the calibration of Hemley, 1987). Unlike Enami et al (2007), we found no correlation between the residual pressure and the size of the inclusions. Table 4.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…For different UHPM complexes the maximum upshift of the main Raman quartz bands (up to 477 cm À1 ) was documented for partly transformed coesite inclusions , corresponding to residual pressures of up to 1.6 GPa, (using the calibration of Hemley, 1987). Unlike Enami et al (2007), we found no correlation between the residual pressure and the size of the inclusions. Table 4.…”
Section: Discussioncontrasting
confidence: 58%
“…The Raman shift of quartz was recently tested on natural samples in order to estimate the effect of peak metamorphic pressure on residual pressure within the quartz inclusions (Enami et al, 2007). For different UHPM complexes the maximum upshift of the main Raman quartz bands (up to 477 cm À1 ) was documented for partly transformed coesite inclusions , corresponding to residual pressures of up to 1.6 GPa, (using the calibration of Hemley, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual pressure retained by quartz completely sealed in garnet was measured using Raman spectra with a parameter of ∆ω 1 = ω 1 standard − ω 1 sample (Enami et al, 2007). The ∆ω 1 values are 5.5 -7.0 cm −1 in the garnet zone samples, and most values in the oligoclase -biotite zone samples are less than 8.5 cm −1 (Fig.…”
Section: Raman Barometrymentioning
confidence: 99%
“…Colomban (2000Colomban ( , 2001 has described this complex picture in an elegant way, invoking several types of chain, sheet and three-dimensional structures labelled Q 0 -Q 4 , which can be assigned as follows: Q 0 , representing monomer SiO 4 units, with bands in the region 850-800 cm −1 ; Q 1 , representing Si 2 O 7 groups, with a band near 950 cm −1 ; Q 2 , silicate chains with bands in the region of 1100-1050 cm −1 ; Q 3 , silicate sheets with a band near 1100 cm −1 ; and Q 4 , representing SiO 2 and tectosilicates with a band in the range of 1250-1150 cm −1 . Additionally, spectral features may arise from crystalline quartz and its modifications caused by pressure or temperature extremes, for which the parent Si=O band occurs at 465 cm −1 (Jayaraman et al 1987;McMillan et al 1992;Schmidt & Ziemann 2000;Enami et al 2007). Figure 2 presents a typical spectrum collected from a glass bubble within a fulgurite specimen.…”
Section: Resultsmentioning
confidence: 99%